A dual colorimetric-ratiometric fluorescent probe NAP-3 for selective detection and imaging of endogenous labile iron(iii) pools in C. elegans12. Issue 24 (25th March 2015) - Goel, Atul; Umar, Shahida; Nag, Pankaj; Sharma, Ashutosh; Kumar, Lalit; Shamsuzzama; Hossain, Zakir; Gayen, Jiaur R.; Nazir, Aamir
<x xml:space="preserve">Abstract</x> The first dual colorimetric and ratiometric fluorescent probe NAP-3 for selective visualization of labile iron(iii) pools in Caenorhabditis elegans is reported.